P63 Adverse pregnancy outcomes and long-term risk of maternal renal disease: a systematic review and meta-analysis. (3rd September 2019) - Barrett, PM; McCarthy, FP; Kublickiene, K; Cormican, S; Judge, C; Evans, M; Kublickas, M; Perry, IJ; Stenvinkel, P; Khashan, AS
Abstract : Background: Adverse pregnancy outcomes, like hypertensive disorders of pregnancy (HDP), gestational diabetes (GDM) and preterm delivery, are associated with increased risk of long-term maternal cardiovascular and cerebrovascular disease. Comparatively little is known about whether adverse pregnancy outcomes increase the risk of maternal renal disease. We aimed to investigate associations between adverse pregnancy outcomes (HDP, GDM, preterm delivery) and long-term maternal chronic kidney disease (CKD) and end-stage kidney disease (ESKD), by synthesising the results of relevant published studies. Methods: A systematic search of PubMed, EMBASE and Web of Science was undertaken from inception of databases to 31 July 2018. Case-control and cohort studies published in English were eligible for inclusion if they provided original effect estimates for associations between adverse pregnancy outcomes (HDP, GDM, preterm delivery) and maternal renal disease (primary outcomes: CKD, ESKD; secondary outcomes: renal hospitalisation, mortality due to renal disease). Two independent reviewers extracted data and assessed risk of bias. Random effects meta-analyses were conducted using RevMan 5.3 to determine the pooled adjusted odds ratio (AOR) and 95% confidence interval (95%CI) for each association between each adverse pregnancy outcome and CKD or ESKD respectively. Subgroup analysis by HDP subtype was performed. Results: Of 5, 120 studies retrieved, 21 studies met inclusion criteria (37 adjusted effect estimates in total, including 4, 483, 847 participants). HDP was associated with significantly increased odds of ESKD (AOR 6.58, 95%CI 4.06–10.65, based on nine effect estimates), CKD (AOR 2.08, 95%CI 1.06–4.10, based on eight estimates), and renal hospitalisation (AOR 2.29, 95%CI 1.42–3.71, based on six estimates). The magnitude of association was dependent on HDP subtype: AOR for preeclampsia and ESKD was 4.87 (95%CI 3.01–7.87); for gestational hypertension and ESKD was 3.65 (95%CI 2.34–5.67); for other HDP (including chronic hypertension ± superimposed preeclampsia) and ESKD was 14.67 (95%CI 3.21–66.97). Preterm delivery was associated with increased odds of ESKD (AOR 2.16, 95%CI 1.64–2.85, based on three estimates). GDM was associated with increased odds of CKD among black women (AOR 1.78, 95%CI 1.18–2.70), but not white/Caucasian women (AOR 0.81, 95%CI 0.58–1.13, based on four estimates). Conclusion: Women who experience adverse pregnancy outcomes have increased odds of long-term renal disease, particularly those exposed to HDP. This study was limited by small numbers of studies in each individual meta-analysis, restricting the ability to assess for publication bias. Long-term follow-up should be optimised for women who experience adverse pregnancy outcomes, and preventive interventions may be warranted to reduce their risk of clinically significant renal disease.